RRR-α-tocopherol as a Predominant Stereo-isomer in Chinese Breast Milk During Lactation Stages (P11-057-19). (13th June 2019) - Cai, Xiaokun; Mao, Yingyi; Tian, Fang; Chen, Lei; Zhao, Yanrong; Wu, Ke; Cai, Meiqin; Guan, Yan
Abstract: Objectives: Human milk is the most important source for neonates to acquire adequate vitamin E for their immune system and brain growth. Among all tocopherols, infant brain discriminates in favor of the natural occurring RRR-α-tocopherol against the synthetic α-tocopherol stereoisomers and other tocopherols. However, the stereoisomer profiles of α-tocopherol in Chinese human milk have not been previously reported. This study aimed to analyze the stereoisomer profile of α-tocopherol in Chinese human milk over different lactation stages. Methods: Colostrum (day 0–7), transitional milk (day 8–15) and mature milk (day 40–45) were collected longitudinally from 89 healthy lactating mothers of full-term, singleton delivery. The levels of α-tocopherol stereoisomers (RRR, RSR, RSS, RRS, Σ2S) were determined by high performance liquid chromatography with fluorescence detection. Results: In three lactation stages, RRR-α-tocopherol is the predominated stereoisomers in Chinese human milk ( P  < 0.0001), accounting for an average proportion of 85% of total α-tocopherol. In contrast, the ratios of the synthetic stereoisomers were RRS, 5.10-6.02%; RSR, 2.32-3.31%, RSS, 2.66-2.85%; and Σ2S, 2.89%-3.49%. The mean total α-tocopherol was 9.20mg/L in colostrum but sharply declined to 4.10 mg/L in mature milk. After taking the different breastfeeding volumes over lactation stages into consideration, Chinese human milk constantly provided about 3.5 mg/day α-tocopherol and 2.98 mg/day RRR-α-tocopherol to infants. Conclusions: RRR-α-tocopherol is the predominated stereoisomer in Chinese human milk over different lactation stages. Chinese breastmilk supply higher % of RRR- stereoisomer as 85% of total α-tocopherol than US report as 75%. There is, therefore, a demand to add matched level of RRR- α-tocopherol in Chinese formula. Funding Sources: Abbott.